Internet connectivity disruption in Syria (Syria) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity mixed detected in Syria. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: SY-2026-0044. Severity: critical. Confidence: 65%